Figurative Language Analysis on Bohemian Rhapsody Song by Queen: Semantics Study - Sherly Tiffany; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
This research purposes to analyze and examine the type’s figurative language that consists in the song, especially in the Bohemian Rhapsody by Queen. Figurative language in Queen song lyrics used to analyze the deeper meaning of words; and it is also used to make the lyrics sound more beautiful. The analysis used a descriptive qualitative research method. This study used descriptive qualitative method. Researched object in this study is figurative language and its meaning with a stylistic review and its implementation. The data used were taken Bohemian Rhapsody song by Queen. Sources of data obtained from song lyrics on the album A Night at the Opera which was the fourth studio album of Queen. Data collection techniques implemented library technique, listening technique and note-taking technique. The data analysis used is a semantics model, especially in the area of figurative language. The result demonstrates that there are three of four types of figurative language occur; 39% of comparison type, 23% of contradiction type, and 38% of repetition type figurative language while correlations type was not found in the analysis. According to the findings of this analysis, figurative language occurs frequently in the type of comparison for percentage of 39% occurrence. It could be concluded that the song commonly contained figurative language, and specifically the song had type of comparison figurative language.